PERLINDUNGAN HUKUM BAGI DEBITUR ATAS PELAKSANAAN LELANG EKSEKUSI HAK TANGGUNGAN TANPA MENGGUNAKAN HARGA LIMIT YANG DITETAPKAN SECARA WAJAR - Santoso, Aan Imam; Yudha Cahya Kumala; Maryano , Maryano (Journal of Innovation Research and Knowledge, 2025)
Article 55 paragraph (1) of PMK No. 122 of 2023 states that every Auction implementation is required to have a Limit Value. However, in practice, the implementation of mortgage execution auctions is often carried out without paying attention to the provisions regarding a reasonable limit price. The formulation of the problem in this study is what are the legal consequences of implementing mortgage execution auctions without using a reasonably determined limit price? And what is the legal protection for debtors for implementing mortgage execution auctions without using a reasonably determined limit price? The theories used in this study are the theory of legal consequences according to R. Soeroso and the theory of legal protection according to Satjipto Rahardjo. The method used in this research is a normative juridical research type in the form of legal materials from libraries or secondary data with primary, secondary and tertiary legal materials sources. The research approach used is a statutory, conceptual, analytical and case approach. The legal material collection technique is carried out by identifying and inventorying positive legal regulations, and researching library materials relevant to the problem. The legal material analysis technique is carried out with systematic legal interpretation, grammatical and analogical construction. The results of the study indicate that the legal consequences of implementing a mortgage auction without using a reasonably determined limit price are that the auction is invalid and has no binding legal force. The unfairness in determining the limit price that is not based on an objective and independent assessment has caused real losses for the debtor. Therefore, this action can be categorized as an unlawful act (onrechtmatige daad). The consequences of this violation not only cause the cancellation of the auction results, but also have an impact on the legal status of the collateral object, which must be returned to its original condition before the auction was conducted. Legal protection for debtors in implementing a mortgage auction without using a reasonably determined limit price is provided in the form of repressive legal protection. This protection allows the aggrieved debtor to file an objection or lawsuit through the courts. The legal basis refers to Article 1365 of the Civil Code concerning unlawful acts, which occur when the execution is carried out without paying attention to the principle of prudence, without involving an independent assessment, or in bad faith. In this context, the debtor can demand the cancellation of the auction results and the restoration of rights to the collateral object that has been auctioned illegally.